Decrease of Irradiated Volume using Rotational Treatment by Avoidance Sector in Radiation Therapy for Esophageal Cancer - 황철환; 김성후; 구재흥; 손종기; Chulhwan Hwang; Seong Hu Kim; Jae Heung Koo; Jong Ki Son (Journal of the Korean Society of Radiology, 2018)
세기변조방사선치료와 입체적세기조절회전치료 시 조사체적과 선량 퍼짐 현상을 줄이기 위한 방법으로 조사 각도를 제한하는 부분 각도에 의한 회전치료 기능을 적용하여 표적체적과 주변 정상장기의 선량에 대해 입체조형방사선치료와 비교 분석하였다. 치료계획에 따른 표적체적의 선량분포는 통계적으로 유의한 차이를 확인할 수 없었으며, 폐의 5 Gy(V5) 체적에서 입체조형방사선치료 56.53%, 세기변조방사선치료 52.03%, 입체적세기조절회전치료 47.84%를 나타내어 유의한 차이를 나타내었다(CRT-IMRT p=0.035, CRT-VMAT p<0.001, IMRT-VMAT p<0.001). 10 Gy 체적(V10)에서는 입체조형방사선치료 35.12%, 세기변조방사선치료 34.04%, 입체적세기조절회전치료 33.28%를 보여, 입체조형방사선치료와 세기변조방사선치료(p=0.018), 입체적세기 조절회전치료(p=0.035)에서 유의한 차이를 나타내었으나 20 Gy 체적(V20)에서는 유의한 선량 차이를 확인 할 수 없었다. 심장의 평균선량과 20 Gy 체적은 치료계획에 따라 유의한 차이를 확인할 수 없었으나, 30, 40 Gy 체적은 입체적세기조절회전치료에서 37.16%, 22.46%를 나타내어 입체조형방사선치료와 비교에서 유의한 차이(p=0.028)를 보였다. 이와 같이 조사체적 감소에 따른 폐의 저 선량 체적(V5, V10)의 감소를 확인할 수 있었으며, 세기변조방사선치료와 입체적세기조절회전치료 시 조사 각도를 일부 제한함으로써 표적체적의 선량분포는 동일하게 유지함과 동시에 조사체적을 줄일 수 있었다. 이로 인해 폐의 선량 퍼짐 현상의 감소로부터 폐의 독성을 낮추는데 기여할 수 있을 것으로 사료된다. In this study, plans to apply 3D conformal radiotherapy, intensity modulated radiotherapy, and volumetric intensity modulated arc radiotherapy to esophageal cancer radiotherapy were compared. In particular, arc therapy was applied to reduce irradiated volume and spread of low-dose during intensity modulated radiation therapy and volumetric intensity modulated arc radiotherapy by limiting part of irradiated angle, in order to compare target doses and dose for surrounding normal tissues of the two methods and those of 3D conformal radiotherapy. No significant difference in target dose was found among the three methods. The 5 Gy volume(V5) of the lung showed 56.53% of conformal radiotherapy, 52.03% of intensity modulated radiotherapy, and 47.84% of volumetric modulated arc therapy(CRT-IMRT p=0.035, CRT-VMAT p<0.001, IMRT-VMAT p<0.001). The 10 Gy volume(V10) showed a significant difference in conformal radiotherapy 35.12%, intensity modulated radiotherapy 34.04%, and volumetric modulated arc radiotherapy 33.28%, showing significant difference in intensity modulated radiotherapy(p=0.018), volumetric modulated arc therapy(p=0.035), no significant difference in dose was found at 20 Gy volume. The mean dose and 20 Gy volume of the heart were not significantly different according to the treatment plan, but the 30 and 40 Gy volumes were 37.16% and 22.46% in the volumetric modulated arc radiotherapy, showing significant differences(p=0.028) in comparison with conformal radiotherapy. It is believed that, by limiting part of the irradiated angle during intensity modulated radiotherapy and volumetric intensity modulated arc radiotherapy, the irradiated volume and, thereby, the 5-10 Gy area and toxicity of the lung can be reduced while maintaining dose distribution of the target dose.